Estrategia evaluativa facilitadora del mejoramiento del resultado en las pruebas ICFES de los estudiantes de la institución educativa Distrital Antonio José de Sucre (2008)
Due to the problems existing in the INSTITUCION EDUCATIVA DISTRITAL ANTONIO JOSE DE SUCRE regarding not get the expected results in tests ICFES in recent years, the directives of the institution concerned with the educational quality of their students were proposed to find the factors that were affecting this generation problematic. That is why this research project aims to propose a strategy evaluative witch result in improved testing ICFES of students at our school. The methodology used in this research work was kind of Ethnography and elected to apply the paradigm Socio-critic, because he needed to study the social or cultural phenomena that occur as a result of the interaction of people in an educational community, leaving aside assumptions own, with the sole purpose of reaching interpret reality. It is important to mention that in implementing the collection techniques was evident that is required to employ a evaluative strategy which itself is a strategy facilitator of the learning process, because they could analyse that the failure that is significantly affecting students' performance when confronted with evidence of state is the lack of ownership of the evaluation methodology used by the ICFES. So one can conclude that the institution needed to implement an educational tool with which Students incorporate this kind of assessment to their everyday life in the classroom, because the fact that only implements this form of assessment in the Pre-Course ICFES is affecting them significantly in their performance in this examination.